AN INTEGRATED CONTROL FRAMEWORK FOR ENHANCING STABILITY AND PRODUCT QUALITY IN DISTILATION COLUMNS - Riny Yolandha Parapat, Devi Alfiani Khoerunnisa, Kylla Almira Rahma Fadillah, Yosanti Iskandariah No (PT Wahana Global Education, 2026)
This research focuses on the design and evaluation of temperature and pressure control schemes for a binary methanol–water distillation column to ensure stable operation and consistent top-product purity. The proposed approach employs Proportional–Integral–Derivative (PID) control strategies embedded in an industrial automation framework. The findings demonstrate that maintaining stable column pressure through a Pressure Indicator Controller (PIC) reduces significant variations in boiling behaviour, while temperature regulation via Temperature Indicator Controllers (TICs) applied to the reboiler and reflux flow effectively preserves the target methanol composition. Furthermore, the coordinated operation of these control loops significantly reduces steady-state error and improves settling time under disturbance conditions. In conclusion, the implementation of robust process control techniques not only improves product quality but also contributes to enhanced energy efficiency in distillation operations.